Potencial hepatoprotetor, antineoplásico e genoprotetor da geoprópolis produzida por abelha jandaíra (melipona subnitida d.) no semiárido do Rio Grande do Norte, Brasil - Paiva, Kaliane Alessandra Rodrigues de (Universidade Federal Rural do Semi-Árido, 2020)
The objective was to evaluate the hepatoprotective potential against injuries induced by acetaminophen, the antineoplastic and genoprotective activity of the hydroethanolic extract of the geopropolis produced by Melipona subnitida D., in the semiarid region of Northeast Brazil. The chemical composition and antioxidant activity of the six samples (A1, A2, A3, A4, A5, A6) of geopropolis hydroethanolic extract were evaluated. The hepatoprotective potential was evaluated through biochemical analysis of liver function, macroscopic, histological and stereological evaluation of the livers in 04 experimental groups (G1- negative control, G2- 50 mg/kg of hydroethanolic extract from geopropolis, G3- 50 mg/kg of hydroethanolic extract of geopropolis and 600 mg/kg of acetaminophen, G4- 600 mg/kg of acetaminophen) consisting of 06 rodents of the species Rattus norvegicus Berkenhout, 1769, Wistar strain, with acute liver damage induced by acetaminophen. The antineoplastic potential was determined by evaluating the cytotoxic effect of the hydroethanolic extract of geopropolis in human hepatocellular carcinoma (HepG2) cell lines and fibroblasts from L929 mice. The genoprotective effect was analyzed in the L929 mouse fibroblast cell line. Samples of the geopropolis hydroethanolic extract showed 41 phenolic compounds, distributed between phenols and flavonoids. The presence of 4- demethyldeoxypodophyllotoxin 4-O-glucopyranoside is reported for the first time in a meliponid geopropolis. Samples A1, A2, A4, A5 and A6 showed moderate antioxidant activity expressed by IC50 values equal to 82.50, 122.20, 98.80, 76.30 and 144.0, respectively, correlated with high levels of total phenols and flavonoids ranging from 16.62 ± 3.91 to 28.46 ± 1.73 and 14.72 ± 3.75 to 32.22 ± 4.43, respectively. The results of the serum levels of the enzymes TGO and TGP of the rats, indicated that the hydroethanolic extract of the geopropolis of M. subnitida D. did not cause hepatotoxicity. In the macroscopic evaluation of the livers, in the G3 group it was possible to observe a pale brown color and slight hemorrhage, in the G4 the presence of hemorrhagic suffusions in the capsule, irregular contours and accentuation of the lobular pattern. In the histoarchitecture of the livers, in G3 it 8 was found foci of tumefied, vacuolized and necrotic hepatocytes, in G4 degeneration and diffuse necrosis of hepatocytes. In stereology, there was an increase in the percentage of hepatocytes and sinusoids, as well as a reduction in collagen in the G3 group compared to G4. The hydroethanolic extract of the geopropolis showed a cytotoxic effect against HepG2 cell line and L929 fibroblasts, after 72 h of exposure, with IC50 values equal to 365.00 and 250.9 μg/mL, respectively. It also had a genoprotective effect, with percentages of genotoxicity reduction of 90.74%, 73.12% and 48.18%, at concentrations of 500, 250 and 100 μl/mL of the extract, respectively. It is concluded that the hydroethanolic extract of the M. subnitida D. geopropolis presents varied chemical composition, high levels of total phenols and flavonoids, hepatoprotective potential against acute liver lesions, cytotoxic effect on neoplastic cells and genoprotective activity, being a promising natural product in chemotherapy
Keywords: Abelha sem ferrão; Genoproteção; Geoprópolis; Lesão hepática; Quimioterápico; Stingless Bee.; Genoprotection.; Geopropolis.; Hepatic lesions.; Chemotherapy; CIENCIAS AGRARIAS::MEDICINA VETERINARIA